Studying in Antarctica the time-frequency characteristics of HF signals at the long radio paths - A. V. Zalizovski; A. V. Koloskov; Y. M. Yampolski (Ukrainian Antarctic Journal, 2015)
The background seasonal and diurnal variations of characteristics of HF radio signals in frequency and time domains propagated at the long radio paths are studied. The signals transmitted bу RWM (frequencies 4996, 9996, аnd 14996 kHz) аnd CHU (frequencies 3330, аnd 7850 kHz) time service radio stations were received at the Ukrainian Antarctic Station (UAS) Akademik Vernadsky in Мау 2010 -April 2011. Average monthly spectrograms of the signals are presented апd analyzed. Pulse selection of the RWM signals allowed detecting the three different pathways: the direct апd reverse paths, lying оn the great circle, апd trajectories nоt belonging to great circle that arisen bу scattering on the ionospheric irregularities of aurora oval. Signals of СНU station propagate to the UAS bу direct path and bу scattering оn ionospheric inhomogeneities of the polar oval. The propagation paths of different components in the signal spectra have been studied. The results of the analyses of the signal propagation described in the paper саn bе used for diagnostics of ionospheric irregularities at the long radio paths.